2005
DOI: 10.1128/mcb.25.13.5355-5362.2005
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Damage-Inducible UbL-UbA Protein Ddi1 Participates in Mec1-Mediated Degradation of Ho Endonuclease

Abstract: Ho endonuclease initiates a mating type switch by making a double-strand break at the mating type locus, MAT. Ho is marked by phosphorylation for rapid destruction by functions of the DNA damage response, MEC1, RAD9, and CHK1. Phosphorylated Ho is recruited for ubiquitylation via the SCF ubiquitin ligase complex by the F-box protein, Ufo1. Here we identify a further DNA damage-inducible protein, the UbL-UbA protein Ddi1, specifically required for Ho degradation. Ho interacts only with Ddi1; it does not interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(137 citation statements)
references
References 71 publications
5
128
0
1
Order By: Relevance
“…The UbL domain of Ddi1 is required for interaction with the 19S RP of the proteasome, and one model for activation of an UbL-UbA protein could be that binding of a K48-linked ubiquitin chain to the UbA domain frees the UbL domain to bind the proteasome. This model is suggested by our finding that Ddi1 can bind ubiquitylated Ho in the absence of its UbL domain (23). Furthermore, the UbL of Rad23 interacts with its UbA domain, and this may represent an inactive form of the protein (37).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The UbL domain of Ddi1 is required for interaction with the 19S RP of the proteasome, and one model for activation of an UbL-UbA protein could be that binding of a K48-linked ubiquitin chain to the UbA domain frees the UbL domain to bind the proteasome. This model is suggested by our finding that Ddi1 can bind ubiquitylated Ho in the absence of its UbL domain (23). Furthermore, the UbL of Rad23 interacts with its UbA domain, and this may represent an inactive form of the protein (37).…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, deletion of the Ufo1 UIMs may be interfering with a function downstream of ubiquitylation. We recently found that the ubiquitin domain protein Ddi1 is required for the final stages of degradation of Ho and that, in the absence of Ddi1, Ho accumulates in a stable ubiquitylated form (23). Ddi1 belongs to a family of UbL-UbA proteins proposed to act as proteasome receptors for ubiquitylated substrates (11,35).…”
Section: Resultsmentioning
confidence: 99%
“…8D). This mechanism would resemble the classical cooperation of a UBL domain with its closely related homolog, the ubiquitin-associated (UBA) domain, which act as a carrier to deliver ubiquitylated substrates to the proteasome (Kaplun et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Rub1 Binds to Non-proteasomal Ub Receptors/ShuttlesThere are three well-studied non-proteasomal Ub receptors/ shuttles: Rad23 (its human orthologue is known as hHR23a) (47,48), Dsk2 (known as hPLIC1 or Ubiquilin 1 (UQ1) in humans) (49), and Ddi1 1 (50,51). All of them are unique in that they contain an N-terminal Ub-like (UBL) domain that binds to the proteasome via Rpn1 (42,52,53) and a C-terminal Ubassociated (UBA) domain that binds to Ub chains (54,55).…”
Section: Rub1 Is Structurally Similar To Ubiquitin-although Rub1 Ismentioning
confidence: 99%